Chemical constituents of garcinia prainiana - Shukranul Mawa,; Ikram M. Said, (Universiti Kebangsaan Malaysia, 2012)
Five compounds identified as friedelin 1, eupha-8, 24- diene 3-β-ol 2, stigmasterol 3, teraxerone 4 and teraxerol 5 have been isolated from Garcinia prainiana (Guttiferae) for the first time. There has been no previous report on the chemical constituents and biological activities of this plant. Compounds 1, 2 & 3 were isolated from the methanol extract of the twigs while compounds 4 & 5 were isolated from the methanol extract of the leaves. The structures for all the compounds were evaluated based on spectroscopic analysis and comparison with the published information in the literature.